2020
DOI: 10.1371/journal.pone.0233153
|View full text |Cite
|
Sign up to set email alerts
|

An empirically derived recommendation for the classification of body dysmorphic disorder: Findings from structural equation modeling

Abstract: Body dysmorphic disorder (BDD), together with its subtype muscle dysmorphia (MD), has been relocated from the Somatoform Disorders category in the DSM-IV to the newly created Obsessive-Compulsive and Related Disorders category in the DSM-5. Both categorizations have been criticized, and an empirically derived classification of BDD is lacking. A community sample of N = 736 participants completed an online survey assessing different psychopathologies. Using a structural equation modeling approach, six theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Similarly, evidence suggests that neuroticism is more strongly associated with symptoms of OCD, hoarding disorder, and BDD than with symptoms of HPD and SPD (Keuthen et al, 2015; Watson et al, 2018). Finally, factor analytic studies have consistently shown that self-reported HPD and SPD symptoms load on a shared underlying “grooming” factor in both clinical and nonclinical samples (Hartmann et al, 2020; Maraz et al, 2017), and this grooming factor has been shown to have relatively limited association with negative emotionality (Snorrason et al, 2021, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence suggests that neuroticism is more strongly associated with symptoms of OCD, hoarding disorder, and BDD than with symptoms of HPD and SPD (Keuthen et al, 2015; Watson et al, 2018). Finally, factor analytic studies have consistently shown that self-reported HPD and SPD symptoms load on a shared underlying “grooming” factor in both clinical and nonclinical samples (Hartmann et al, 2020; Maraz et al, 2017), and this grooming factor has been shown to have relatively limited association with negative emotionality (Snorrason et al, 2021, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Prospectively, we should also examine potential additional effects of exposure and response prevention exercises in this subclinical target group. In accordance with the suggested body image disorders spectrum ( Hartmann et al, 2020 ), we may add examples of weight-based concerns to the exercises in order to test whether individuals at risk of an eating disorder can also benefit from AINA. In general, future studies should examine differential effects of the modules and strategies in dismantling designs.…”
Section: Discussionmentioning
confidence: 99%
“…It proposed reconceptualising MD within the spectrum of ED from a transdiagnostic perspective (Murray et al, 2013) or grouping MD and ED together under the category of "body image disorders" (Cooper et al, 2020). This proposal has been empirically validated by Hartmann et al (2020).…”
Section: Muscle Dysmorphia: a Pathological Extreme Of Male Body Dissa...mentioning
confidence: 99%